Voltammetric characteristics of miconazole and its cathodic stripping voltammetric determination - PEREIRA,FRANCISCO C. (2002)
Miconazole is reduced at mercury electrode above pH 6 involving organometallic compound formation, responsible for an anomalous polarographic behavior. The electrodic process presents a large contribution of the adsorption effects. The drug can be determined by cathodic stripping voltammetry from 8.0 x 10-8 to 1, 5 x 10-6 molL-1 in Britton-Robinson buffer pH 8.0, when pre-accumulated for 30s at an accumulation potential of 0V. A relative standard deviation of 3.8% was obtained for ten measurements of 1.0 x 10-7 molL-1 miconazole in B-R buffer pH 8.0 and a limit detection of 1, 7 x 10-8 molL-1 was determined using 60s of deposition time and scan rate of 100 mVs-1. The proposed method is simple, precise and it was applied successfully for the determination of the miconazole in pure form and in commercial formulations, showing mean recoveries of 99.7-98.4%.